2022
DOI: 10.21608/eijest.2022.114803.1123
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Spatial Autocorrelation of Surface-Air Temperature for Different Ground Materials in Hot Desert Climate

Abstract: Several studies have been conducted in recent decades to investigate how different pavements affect the microclimate conditions and thermal comfort for humans. However, few studies explore how different ground materials are associated with surface and air temperature spatially. This paper examines and quantifies the micro-scale influence of various ground surface materials on the microclimate conditions in a hot desert climate, like Aswan City. This study applied several methods and techniques such as; on-site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…The absence of green spaces primarily contributes to thermal discomfort in urban outdoor environments. Numerous studies have indicated that urban areas in warm climatic conditions tend to use limited spaces by substituting heat-absorbing land surfaces with natural cover [4][5][6]. This phenomenon occurred because of the substitution of indigenous plants with surfaces that possess the capacity to assimilate solar radiation and retain heat.…”
Section: Of 23mentioning
confidence: 99%
“…The absence of green spaces primarily contributes to thermal discomfort in urban outdoor environments. Numerous studies have indicated that urban areas in warm climatic conditions tend to use limited spaces by substituting heat-absorbing land surfaces with natural cover [4][5][6]. This phenomenon occurred because of the substitution of indigenous plants with surfaces that possess the capacity to assimilate solar radiation and retain heat.…”
Section: Of 23mentioning
confidence: 99%